Comparison of accuracy of selected models of time series at development of the Czech national bank assets - Linda, Bohdan; Kubanová, Jana (Univerzita Pardubice, 2007)
A lot of ways how to estimate the values of the time series for the future period are known. The basic approach starts from principle of linear regression methods. The Box- Jenkins methodology is very often used in financier when the time series are analysed. The paper deals with application of the bootstap principle in this methodology. The classical and resampling methods are compared at extrapolation of the values of the time series of assets of the Czech national bank.
Keywords: extrapolation; parameters estimate; bootstrap method; autoregressive models; moving blocks overlapping and not overlapping methods